An Exploratory Examination and Critique of Academic Law Librarian Blogs: A Look into an Evolving Reference Communication Practice. Issue 2 (3rd April 2017) - Jackson-Brown, Grace M.
ABSTRACT: This study is an exploratory qualitative investigation of academic library blogs with the purpose of examining how the technology of blogging is evolving for reference and research purposes at particular academic law libraries. This study uses anthropological archive research methods to study the blogs' posts and triangulates the study with librarian blogger interviews. It provides a look into possible future directions for blogging in academic law libraries that may serve as a model for other academic libraries.